(五分之一+七分之一+九分之一+十一分之一)×(七分之一+九分之一+十一分之一+十三分之一)-(五分之一+七分之一+九分之一+十一分之一+十三分之一)×(七分之一+九分之一+十一分之一)
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/01 20:23:26
(五分之一+七分之一+九分之一+十一分之一)×(七分之一+九分之一+十一分之一+十三分之一)-(五分之一+七分之一+九分之一+十一分之一+十三分之一)×(七分之一+九分之一+十一分之一)
(五分之一+七分之一+九分之一+十一分之一)×(七分之一+九分之一+十一分之一+十三分之一)-(五分之一+七分之一+九分之一+十一分之一+十三分之一)×(七分之一+九分之一+十一分之一)
(五分之一+七分之一+九分之一+十一分之一)×(七分之一+九分之一+十一分之一+十三分之一)-(五分之一+七分之一+九分之一+十一分之一+十三分之一)×(七分之一+九分之一+十一分之一)
设x=五分之一+七分之一+九分之一+十一分之一
y=七分之一+九分之一+十一分之一
(五分之一+七分之一+九分之一+十一分之一)×(七分之一+九分之一+十一分之一+十三分之一)-(五分之一+七分之一+九分之一+十一分之一+十三分之一)×(七分之一+九分之一+十一分之一)
=x(y+1/13)-(x+1/13)y
=xy+1/13x-xy-1/13y
=1/13x-1/13y
=1/13(x-y)
=1/13×1/5
=1/65
设x=五分之一+七分之一+九分之一+十一分之一 y=七分之一+九分之一+十一分之一(五分之一+七分之一+九分之一+十一分之一)×(七分之一+九分之一+十一分之一+十三分之一)-(五分之一+七分之一+九分之一+十一分之一+十三分之一)×(七分之一+九分之一+十一分之一)=x(y+1/13)-(x+1/13)y=xy+1/13x-xy-1/13y=1/13x...
全部展开
设x=五分之一+七分之一+九分之一+十一分之一 y=七分之一+九分之一+十一分之一(五分之一+七分之一+九分之一+十一分之一)×(七分之一+九分之一+十一分之一+十三分之一)-(五分之一+七分之一+九分之一+十一分之一+十三分之一)×(七分之一+九分之一+十一分之一)=x(y+1/13)-(x+1/13)y=xy+1/13x-xy-1/13y=1/13x-1/13y=1/13(x-y)=1/13×1/5=1/65
收起